Back Cover: Acetylcholinesterase‐Catalyzed Hydrolysis Allows Ultrasensitive Detection of Pathogens with the Naked Eye (Angew. Chem. Int. Ed. 52/2013). Issue 52 (11th December 2013) - Liu, Dingbin; Wang, Zhantong; Jin, Albert; Huang, Xinglu; Sun, Xiaolian; Wang, Fu; Yan, Qiang; Ge, Shengxiang; Xia, Ningshao; Niu, Gang; Liu, Gang; Hight Walker, A. R.; et al.
<x xml:space="preserve">Abstract</x> A new colorimetric assay for pathogen detection is described by X. Chen et al. in their Communication on page 14065 ff. An improved heterogeneous sandwich‐type ELISA enhances detection sensitivity by a two‐step signal amplification process involving gold particle aggregation induced by acetylcholinesterase‐catalyzed hydrolysis, which leads to a color change, followed by enrichment of the analyte using magnetic beads. This assay is as sensitive as RT‐PCR, but more convenient and less expensive.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>